Experience-Regulated Neuronal Signaling in Maternal Behavior - Fuentes, Ileana; Morishita, Yoshikazu; Gonzalez-Salinas, Sofia; Champagne, Frances A.; Uchida, Shusaku; Shumyatsky, Gleb P. (Frontiers in Molecular Neuroscience, 2022)
Maternal behavior is shaped and challenged by the changing developmental needs of offspring and a broad range of environmental factors, with evidence indicating that the maternal brain exhibits a high degree of plasticity. This plasticity is displayed within cellular and molecular systems, including both intra- and intercellular signaling processes as well as transcriptional profiles. This experience-associated plasticity may have significant overlap with the mechanisms controlling memory processes, in particular those that are activity dependent. While a significant body of work has identified various molecules and intracellular processes regulating maternal care, the role of activity- and experience-dependent processes remains unclear. We discuss recent progress in studying activity-dependent changes occurring at the synapse, in the nucleus and during the transport between these two structures in relationship to maternal behavior. Several pre- and postsynaptic molecules as well as transcription factors have been found to be critical in these processes. This role reflects the principal importance of the molecular and cellular mechanisms of memory formation to maternal and other behavioral adaptations.